Lower urinary tract development and disease. (13th February 2013) - Rasouly, Hila Milo; Lu, Weining
Abstract: Congenital anomalies of the lower urinary tract (CALUT) are a family of birth defects of the ureter, the bladder, and the urethra. CALUT includes ureteral anomaliesc such as congenital abnormalities of the ureteropelvic junction (UPJ) and ureterovesical junction (UVJ), and birth defects of the bladder and the urethra such as bladder‐exstrophy‐epispadias complex (BEEC), prune belly syndrome (PBS), and posterior urethral valves (PUVs). CALUT is one of the most common birth defects and is often associated with antenatal hydronephrosis, vesicoureteral reflux (VUR), urinary tract obstruction, urinary tract infections (UTI), chronic kidney disease, and renal failure in children. Here, we discuss the current genetic and molecular knowledge about lower urinary tract development and genetic basis of CALUT in both human and mouse models. We provide an overview of the developmental processes leading to the formation of the ureter, the bladder, and the urethra, and different genes and signaling pathways controlling these developmental processes. Human genetic disorders that affect the ureter, the bladder and the urethra and associated gene mutations are also presented. As we are entering the postgenomic era of personalized medicine, information in this article may provide useful interpretation for the genetic and genomic test results collected from patients with lower urinary tract birth defects. With evidence‐based interpretations, clinicians may provide more effective personalized therapies to patients and genetic counseling for their families. WIREs Syst Biol Med 2013, 5:307–342. doi: 10.1002/wsbm.1212 This article is categorized under: Developmental Biology > Developmental Processes in Health and Disease Translational, Genomic, and Systems Medicine > Translational Medicine